Physiological pharmacology : a comprehensive tratise. Volume 1-3, The nervous system. Part A-B, Central nervous system drugs. Part C, Autonomic nervous system drugs - Root, Walter S; Hofmann, Frederick G (Academic Press, 1963)
Volume I: The Nervous System - Part A and Volume III: The Nervous System - Part C focus on the effects of drugs on the functions of the central nervous system and the autonomic central nervous systém, respectively. The selection is a reference for readers interested in the effects of drugs on the central nervous system.
Physiological pharmacology
Keywords: Central Nervous System Depressants; farmacie a farmakologie; Central Nervous System Stimulants; Autonomic Nervous System; Neuromuscular Blocking Agents; Cholinergic Agents; autonomní nervový systém; stimulanty centrálního nervového systému; nervosvalové blokátory; Central Nervous System; Central Nervous System Agents; léčivé přípravky; látky tlumící činnost CNS; látky ovlivňující centrální nervový systém; Pharmaceutical Preparations; cholinergní látky; centrální nervový systém